THE METHODOLOGY OF FORMING PEDAGOGICAL VALUES IN STUDENTS OF SPECIALIZED SCHOOLS IN UZBEK LANGUAGE AND LITERATURE LESSONS - Qurbonova Maftuna Faxriddinovna (Modern American Journals, 2025)
This article discusses the methodology of forming pedagogical values in students of specialized schools in Uzbek language and literature lessons. It is argued that organizing methodological work based on pedagogical values in specialized schools fosters friendly relations and human qualities in students, leading to positive results and creating opportunities for their participation in large and small groups.
Keywords: Specialized school, pedagogical value,